2018
DOI: 10.17770/sie2018vol1.3268
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characteristics and Anaerobic Power of Lower Limbs and Their Relationships With Race Time in Female Speed Climbers

Abstract: Previous research indicates that high results in speed climbing are determined by a high level of explosive strength and muscle power in the lower limbs. However, a literature review shows that no studies have analysed women practicing this climbing discipline. Therefore, the main goal of the study was to assess the level of development of physique and the level of explosive strength and muscle power of the lower limbs of female speed climbers at a representative level. Furthermore, an attempt was made to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Speed climbing consists in covering the competition distance in the shortest possible time. Current research indicates that in speed climbing the important motor factors determining sports success are: a high level of explosive strength and a high level of lower limb muscle power (Krawczyk, Ozimek, & Rokowski, 2015;Krawczyk, Ozimek, Rokowski, Pociecha, & Draga, 2017;Krawczyk & Ozimek, 2014;Krawczyk, Ozimek, Rokowski, Pociecha, & Draga, 2018). Some studies have shown that body proportions can be of considerable importance in sport climbing Tomaszewski, Gajewski, & Lewandowska, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Speed climbing consists in covering the competition distance in the shortest possible time. Current research indicates that in speed climbing the important motor factors determining sports success are: a high level of explosive strength and a high level of lower limb muscle power (Krawczyk, Ozimek, & Rokowski, 2015;Krawczyk, Ozimek, Rokowski, Pociecha, & Draga, 2017;Krawczyk & Ozimek, 2014;Krawczyk, Ozimek, Rokowski, Pociecha, & Draga, 2018). Some studies have shown that body proportions can be of considerable importance in sport climbing Tomaszewski, Gajewski, & Lewandowska, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Young climbers, show a slimmer body shape and fall into the ideal or normal category (Michael et al, 2019b). Smaller body sizes allow the climber to perform faster and achieve better times in speed climbing (Krawczyk et al, 2018). The results of this study indicated that the height of rock climbing athletes is more supportive in the speed climbing category.…”
Section: Resultsmentioning
confidence: 76%
“…Rock climbing is a sport that is increasingly popular in the world (Michael et al, 2019a;Michael et al, 2019b) as evidenced by the increased interest after rock climbing became one of the sports contested the 2020 Tokyo Olympics which consists of three categories, namely boulder, speed, and lead climbing (Krawczyk et al, 2018;Pyszczek et al, 2019). The competition format combines the three rock climbing categories (combined format) during the 2020 Tokyo Olympics (Krawczyk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that the main bioenergetic source in speed climbing is the anaerobic lactate system (Krawczyk et al, 2018). Furthermore, some research showed that anaerobic power are factor which may affects the sport results in speed climbing .…”
Section: Introductionmentioning
confidence: 99%